Efficacy of Spinosad and Abamectin against Different Populations of Red Flour Beetle Tribolium castaneum Herbst in Treated Wheat Grain - Andrić, Goran G; Kljajić, Petar J; Pražić Golić, Marijana P (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The efficacy of spinosad and abamectin against T. castaneum adults from a laboratory population with normal susceptibility to contact insecticides and against malathion-resistant populations from Nikinci and Jakovo was tested in the laboratory (25±1ºC and 60±5% r.h.). The insecticides were applied to 500 g of untreated wheat grain for each of the following application doses: 0.25, 0.5, 1.0, 2.5 and 5.0 mg a.i./kg. After treatment, wheat was divided into three equal subsamples and 50 T. castaneum adults from each of the three test populations were released the next day into jars for each dose. Mortality was evaluated after 7, 14 and 21 days of exposure to treated wheat grain. Generally, higher concentrations and longer exposure periods resulted in higher efficacy of both insecticides, but abamectin was significantly more effective than spinosad against all three tested populations. After 7 days of exposure, mortality did not exceed 30% in any test variant. Fourteen days after treatment with the highest dose (5 mg/kg) of spinosad, mortality was highest (75%) in the laboratory population, while treatment with the same dose of abamectin achieved the highest mortality (58%) in the laboratory and Jakovo populations. After 21 days, spinosad applied at the rate of 5 mg/kg was most effective (97% mortality) in the laboratory population, while 88% efficacy was recorded in Jakovo population and 87% in Nikinci population. Abamectin doses of 2.5 and 5 mg/kg caused high adult mortality of 94-100% in the laboratory and Jakovo populations, and a significantly lower mortality in Nikinci population (75 and 86%, respectively). Statistically significant differences in the efficacy of spinosad, and particularly of abamectin, were detected among the three tested populations, the greatest difference being between the laboratory and Nikinci populations, which clearly indicates that resistance of T. castaneum adults to malathion had a significant influence.